PENGGUNAAN SOFTWARE KINOVEA SEBAGAI ALAT KAJIAN TEORITIS MATERI FLUIDA DINAMIS - Tri Wahyuni Purbasari; Sri Handono Budi Prastowo; Trapsilo Prihandono (JURNAL PEMBELAJARAN FISIKA, 2018)
AbstractThis study focused on the theoretical study of PDAM water flow using kinovea software. Software kinovea is a vidio analysis software that can be used to analyze movement. This study aims to assess kinovea software using dynamic fluid concept, and after got the result of video analysis through kinovea software then the result is comparing with the manually calculation. The type of this research is descriptive research. Techniques of data collection are documentation, vidio analysis using kinovea software, mathematical measurement. The result of this study shows that kinovea software is not suitable for video analysis of PDAM water flow, because of the difference between video analysis and manual calculation. Kinovea software can only be used to analyze a movement as in physics concept that is parabolic motion for example on volleyball or basketball which can be analyzed movement speed of a ball. This research can be concluded: Firstly, kinovea software can not be used to analyze dynamic fluid concept in PDM water flow. Secondly, the kinovea software can be used for other researchers to analyzed a parabolic movement such as a sporting movement on volleyball and basketball.Key word: Software kinovea , video analysis, PDAM water flow, dynamic fluid